Adenocarcinoma of the lung presenting with atypical cystic brain lesions - Costa, Ricardo (BMJ Publishing Group, 2014)
Brain metastases occur in up to 10–30% of patients with cancer. Metastatic lesions are usually diagnosed as multiple mass lesions at the junction of the grey and white matter with associated perilesional vasogenic oedema. Cysticercosis is an endemic disease in underdeveloped countries of Africa, Central and South America and is the most common parasitic infection of the central nervous system. The classical radiological finding of neurocysticercosis is cystic lesions showing the scolex in the brain parenchyma. We report a case of metastatic adenocarcinoma of the lung presenting with cystic brain lesions mimicking neurocysticercosis.